UHT treatment and storage of liquid infant formula affects protein digestion and release of bioactive peptides. Issue 1 (14th December 2021) - Ye, Yuhui; Engholm-Keller, Kasper; Fang, Yajing; Nielsen, Christian Fiil; Jordà, Ariadna; Lund, Marianne N.; Chatterton, Dereck E. W.
Abstract : UHT treatment and storage affect IF protein digestibility and the release of bioactive peptides due to structural changes and crosslinkings. Abstract : Ready-to-feed liquid infant formulas (IF) were subjected to direct (D) or indirect (ID) ultra-high-temperature (UHT) treatment and then stored at 40 °C under aseptic conditions for 60–120 days simulating global transportation which accelerates the Maillard reaction. Low pasteurized and unstored IF (LP) was included as a control for the UHT treatments. Simulated infant in vitro digestion was conducted. SDS-PAGE indicated that protein aggregate formation correlated with thermal treatment, being greatest after 60 days of storage. Limited protein digestion was observed after pepsin treatment for 2 h. Beta-lactoglobulin (β-Lg), alpha-lactalbumin (α-La) and protein aggregates remained undigested after 2 h of pepsin digestion in LP and D, but less β-Lg and α-La remained in ID. The digestion of β-Lg and α-La was enhanced in D and ID stored for 60 days, but aggregates remained undigested. After pepsin and pancreatin digestion, large amounts of β-Lg remained undigested in the LP, but digestion increased after UHT treatment (ID > D) and increased further after storage for 60 and 120 days, indicating that heat treatment and storage facilitate the digestion of unaggregated proteins. No aggregates remained after pancreatin digestion of LP, D, ID and D stored for 60 days, but were present in ID stored for 60 days. Aggregates were mainly disulphide-linked, but dityrosine linkages were detected in D and ID stored for 120 days. LC-MS/MS indicated limited proteolysis arising from endogenous milk proteases prior to in vitro digestion, being highest in D. Peptide numbers increased following pepsin and further during pancreatin digestion (β-casein > β-Lg > β-La), and released β-Lg peptides, typically 5–8 amino acids in length, contained several bioactivities, e.g., dipeptidyl-peptidase IV (DPP-IV) and angiotensin converting enzyme (ACE) inhibition.